Long Non-Coding RNA AP000695.2 Acts as a Novel Prognostic Biomarker and Regulates the Cell Growth and Migration of Lung Adenocarcinoma - Wang, Chunyan; Guo, Jishu; Jiang, Rongyan; Wang, Chenyang; Pan, Chenglong; Nie, Zhi; Jiang, Xiulin (Frontiers in Molecular Biosciences, 2022)
Long non-coding RNAs (lncRNAs) are tumor-associated biological molecules and have been found to be implicated in the progression of lung adenocarcinoma (LUAD). LncRNA-AP000695.2 (ENSG00000248538) is a long non-coding RNA (lncRNA) that is widely increased in many tumor types including lung adenocarcinoma (LUAD). However, the aberrant expression profile, clinical significance, and biological function of AP000695.2 in human lung adenocarcinoma (LUAD) need to be further investigated. This study mined key prognostic AP000695.2 and elucidates the potential role and molecular mechanism of AP000695.2 in regulating the proliferation and metastasis of LUAD. Here, we discovered that AP000695.2 was significantly up-regulated in lung adenocarcinoma tissues compared to healthy adjacent lung tissue and higher in LUAD cell lines compared to normal human bronchial epithelial cell lines. Higher expression of AP000695.2 was positively correlated with aggressive clinicopathological characteristics, and AP000695.2 served as an independent prognostic indicator for overall survival, disease-free survival and progression-free survival in patients with LUAD. Receiver operating curve (ROC) analysis revealed the significant diagnostic ability of AP000695.2 (AUC = 0.838). Our in vivo data confirmed that AP000695.2 promotes the proliferation, migration, and invasion of LUAD cells. GSEA enrichment results suggested that AP000695.2 co-expressed genes were mainly enriched in immune-related biological processes such as JAK-STAT signaling pathway and Toll-like receptor signaling pathway. Single sample GSEA analysis showed that AP000695.2 is correlated with tumor-infiltrating immune cells in lung adenocarcinoma. Our findings confirmed that AP000695.2 was involved in the progression of lung adenocarcinoma, providing a novel prognostic indicator and promising diagnostic biomarker in the future.